From Kyoto to Paris - a review of South Africa's climate change response with particular emphasis on the Clean Development Mechanism and envisaged transition to the Sustainable Development Mechanism - Steenkamp, Lee-Ann (Institute of Marine and Environmental Law, 2018)
The climate change timeline is at critical juncture as policymakers, academics and other climate-related stakeholders are contemplating the transition from the Kyoto era to the advent of the landmark 2015 Paris Agreement on Climate Change (the Paris Agreement). The study focuses in particular on tracing the development of and learning from past experience with the Clean Development Mechanism (CDM) - one of the flexible mechanisms provided for in the Kyoto Protocol and tailored specifically for reducing emissions in developing countries. This is undertaken with a view to drawing lessons for its apparent successor, the Sustainable Development Mechanism (SDM) provided for in the Paris Agreement. The study is undertaken against the backdrop of the theoretical framework of market-based instruments supplementing the traditional command-and-control approach to reducing carbon emissions, specifically in the area of environmental taxes and carbon offsets. While it is acknowledged that the major difference between the proposed SDM and the existing CDM is that carbon markets will no longer be limited to developed country parties in that developing countries will also be able to participate, many uncertainties remain. Moreover, while it is uncertain at the time of writing (mid-2017) whether the CDM will continue to exist alongside the SDM or will be replaced by it, the study investigates, among other things, questions around if and how the SDM refines and streamlines the CDM. It considers these questions in the context of not only the relevant international instruments, but more specifically against the backdrop of South Africa's climate-related laws and policy frameworks. It is posited that the CDM - and by extension the SDM - will come increasingly under the spotlight in South Africa, as it will serve as a useful mechanism for reducing (or offsetting) the impending carbon tax liability. The thesis finds that many of the principles listed for the SDM mirror those of the CDM. Yet, some sort of transition from Kyoto to Paris will be required to ensure that the SDM will realise its potential to mitigate emissions and support sustainable development.